2011
DOI: 10.1258/ijsa.2011.011134
|View full text |Cite
|
Sign up to set email alerts
|

Seven days of doxycycline is an effective treatment for asymptomatic rectal Chlamydia trachomatis infection

Abstract: There are no evidence-based guidelines for the specific management of rectal Chlamydia trachomatis (CT) infection. All men who have sex with men (MSM) diagnosed with asymptomatic rectal CT by nucleic acid amplification test (NAAT) at a large London genitourinary (GU) medicine clinic between September 2006 and September 2009 were offered oral doxycycline 100 mg twice daily for seven days and invited for a test of cure (TOC) by CT NAAT four weeks after treatment. A total of 487 asymptomatic rectal CT infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
0
26
2
1
Order By: Relevance
“…Of these 15, four elected to be re-treated with doxycycline rather than have to return at 6 weeks for a test of cure (TOC). [8][9][10][11] Table 2 shows the results of the 11 TOCs. Four out of the nine TOCs were positive, but two had been at risk of re-infection (having reported sex with new partners).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 15, four elected to be re-treated with doxycycline rather than have to return at 6 weeks for a test of cure (TOC). [8][9][10][11] Table 2 shows the results of the 11 TOCs. Four out of the nine TOCs were positive, but two had been at risk of re-infection (having reported sex with new partners).…”
Section: Resultsmentioning
confidence: 99%
“…Those who were RCt positive and who had been treated with azithromycin were invited/recalled for a test of cure at 6 weeks. [8][9][10][11] The number of polymerase chain reaction (PCR) amplification cycles for each RCt positive sample was obtained from the laboratory. The upper limit of amplification cycles that determines positivity in our laboratory is 40.…”
Section: Methodsmentioning
confidence: 99%
“…7,8,10 Emerging data suggest increased failure rates with oral azithromycin compared to doxycycline when used for the treatment of rectal CT infections. [24][25][26][27] Suboptimal treatment efficacy with azithromycin against rectal infections could have important implications for women who may be infected with CT at both urogenital and rectal sites, especially if the latter go unrecognized due to absent testing. If treated with azithromycin, these women could potentially have successful clearance of the urogenital infection, but not necessarily the rectal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Three were retrospective studies of azithromycin or doxycycline for rectal CT infection in asymptomatic men who have sex with men (MSM) that reported estimated efficacy based on repeat rectal CT NAAT [11][12][13]. Drummond et al reported an estimated azithromycin efficacy of 94% in 85 MSM, although the study was limited by the long interval until repeat CT PCR (45% had repeat testing performed >12 weeks after azithromycin treatment) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Steedman et al reported an estimated azithromycin efficacy of 87% in 68 MSM, but 8 of the 9 MSM with a repeat positive CT PCR postazithromycin reported sexual activity between treatment and repeat testing; in addition, 3 of 9 men with repeat positive CT had their repeat test performed ≤21 days posttherapy, introducing the possibility of a false-positive CT NAAT [12]. Elgalib et al reported an estimated doxycycline efficacy of 98.8% in 165 MSM, although the study was limited in that the majority of rectal CT-infected patients initially evaluated were excluded from the efficacy analysis and there was a long interval until repeat CT NAAT was performed (median 45 days) [13]. The fourth study of rectal CT therapy was a prospective observational study in MSM and women by Hathorn et al in which 42 subjects receiving azithromycin and 40 receiving doxycycline during different study phases had an estimated efficacy, adjusting for possible reinfection, of 79% and 100%, respectively, at 6 weeks posttherapy [14].…”
mentioning
confidence: 99%